La SAS en el derecho societario colombiano: de un institucionalismo de forma hacia un nuevo contractualismo (2016)
Without doubt, the provisions contained in Act 1258 of 2008 constitute a true evolution of company law in Colombia, and this is so for several reasons: (i) For trying to take the lead on the subject has been developed in comparative law, (ii)Why try to offer real and effective tools for entrepreneurs of our country, (iii) the novelty of a number of its institutions and, (iv) For above all and, in my opinion, through the law which created the simplified joint stock company in Colombia, is a proposal back to the contract, trying to regain the right of companies to private law, in response to the crisis of institutional theories-formal, material never - company law in our country, than trying to correct the excesses of the market, they give the principle of private autonomy and individual freedom affected, causing lethargy step in the way of making and understanding the right societies, and affecting the promotion and development of the Colombian company. In implementing this Article shall be a brief study of the principle of private autonomy, will address the concept of social interest, and in this way study the theory of contract, institutionalists and neo contractarian corporate law, their background, concept, consequences and manifestations in the Colombian corporate law. Likewise, we will study the origins and history of the Colombian law simplified joint stock company, will be a critical analysis of some of its provisions, taking as reference the legislation, jurisprudence and doctrine that preceded it, and in this way determine the constitutionality of the rules of coverage, the contribution offered by the development of the Colombian corporate law and provides the business contribution of country, mainly as a result of having been granted to the provisions of the 1258 law "eminently device ... so they can be replaced by other provisions agreed upon by the shareholders ", which I intend to prove that the law of simplified joint stock company in Colombia is a proposed new institutionalism contractualism against a form.